Extending Outcome-Based Education through an Embodied Multicultural Learning Framework in Practice-Based Higher Education - I Ketut Sariada; Ida Bagus Gede Surya Peradantha; Rahim Rahiminejat (Journal of Innovation in Educational and Cultural Research, 2026)
This study examines how multicultural learning is articulated and enacted within Outcome-Based Education (OBE) in practice-based higher education and develops an Embodied Multicultural Learning Framework based on the findings. Although OBE emphasizes clearly articulated, measurable learning outcomes, limited attention has been given to how multicultural learning unfolds in embodied studio practices. Using an interpretive qualitative case study design, this research analyses a course syllabus and semi-structured interviews with ten undergraduate students at ISI Bali. The findings show that multicultural competencies are indirectly embedded within general ethical and professional learning outcomes, while assessment criteria primarily prioritize technical performance. At the same time, students experience multicultural learning through bodily adaptation, shifting insider–outsider positioning, peer interaction, and reflective reinterpretation of cultural meaning during studio practice. The study concludes that multicultural learning in practice-based disciplines cannot be fully captured by formal outcome indicators alone, as it develops through embodied and relational processes. This research contributes to the field by proposing a conceptual framework integrating curriculum articulation, embodied engagement, relational negotiation, and reflective integration to inform curriculum design and assessment in practice-based education.